Social Function of BMT In The Cash Waqf Management - Irfan Salim (Jurnal Ilmiah Ekonomi Islam, 2022)
Poverty alleviation can be done through the social function of Baitul Maal wat Tamwil (BMT) such as the management and development of cash waqf. In this case, the government has issued several regulations to support the management and development of cash waqf. This study aims to analyze the social function of BMT Artha Amanah Bantul based on the management and development aspects of cash waqf in accordance with the Indonesian laws and regulations. This research is descriptive qualitative research with interview data collection methods conducted on the administrator of BMT and wakif. The results showed that the management and development of cash waqf in BMT Artha Amanah Bantul has included planning, organizing, leadership, and controlling, while the development of cash waqf covered management patterns, the welfare of nazir, and transparency and accountability. But some efforts to manage and develop the cash waqf undertaken by BMT Artha Amanah Bantul were still not in accordance with the applied laws and regulations. These incompatibilities have implications for the management and development of cash waqf. However, it can be concluded that the management and development of cash waqf in BMT Artha Amanah Bantul based upon the laws and regulations in Indonesia has reflected the social function of BMT.